Motion control shoe affects temporal activity of quadriceps in runners - Cheung, R. T. H.; Ng, G. Y. F (British Journal of Sports Medicine, 2009)
Objective: Delay onset of the vastus medialis obliquus (VMO) has often been reported to happen in people with patellofemoral pain (PFP). Previous studies revealed that a motion control shoe could check rearfoot pronation in overpronators. Literature suggested that movements of the lower leg could affect patellar tracking; thus motion control shoe may help prevent PFP by controlling excessive foot movements. This study aimed to compare the vasti muscle activities in people with excessive foot pronation when running with different footwear.